Manajemen Rantai Pasok Digital dalam Budidaya Jangkrik: Peluang dan Tantangan - Sutariyono Sutariyono; Afandi Rachman; I Dewa Ketut Suharjana; Moehamad Reza Arfiansyah; Siskamto Siskamto (Jurnal Manajemen Bisnis Digital Terkini, 2024)
Digital supply chain management (MRPD) has become an important focus in the context of insecticide farming such as cicada cultivation. This study aims to explore the opportunities and challenges of MRPD implementation in cicada cultivation. The aim is to identify potential improvements in operational efficiency and risk management through the integration of digital technology in the cricket supply chain. The study is scheduled to be conducted for six months, with the initial phase of research focusing on literature analysis and conceptual framework, followed by primary data collection through interviews and survey. The subjects of the study include cricket farmers, feed suppliers, distributors, and end consumers. The research methods used are qualitative and quantitative approaches to gain an in-depth understanding of stakeholders' perspectives and experiences. The results of the study are expected to provide valuable insights into the benefits and constraints of implementing MRPD in cicada cultivation, as well as practical recommendations for industry stakeholders.